The Weakness of the German Car Industry and its Sectoral and Global Impacts - Jo\~ao Leal; Robert Lehmann; Bertrand Marc; Timo Wollmershäuser; Przemyslaw Wozniak (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Industrial production in the German car industry dropped by 9.4% in the third quarter~2018 mainly due to problems with the implementation of the new Worldwide~Harmonized Light-Duty Vehicles Test Procedure (WLTP). As the car producing industry~is the most important sector for the German economy and is deeply integrated into~international value-added chains, this policy report presents estimated sectoral and~global impacts due to this sharp drop. The most affected sectors are fabricated metals~and rubber and plastic products, both in Germany and its main partners, that deliver~intermediate inputs (for example, the Czech Republic). From a global perspective, the~largest effect on gross domestic product (GDP) is – with -0.75% – estimated for~Germany. On top, the three most affected countries are the Czech Republic (-0.21%),~Hungary (-0.20%) and Slovakia (-0.18%).
Keywords: 330